Embodied energy as key parameter for sustainable materials selection: The case of reusing coal fly ash for removing anionic surfactants. (10th January 2017) - Zanoletti, Alessandra; Federici, Stefania; Borgese, Laura; Bergese, Paolo; Ferroni, Matteo; Depero, Laura Eleonora; Bontempi, Elza
Abstract: Coal fly ash (CFA) is an industrial by-product derived from coal combustion in thermal power plants. This abundant and low cost by-product is generally reemployed as an additive in the building industry. This work explores the possibility of recovering CFA as an adsorbing material for the removal of anionic surfactants dissolved in water, on the basis of data about concerning its embodied energy. Indeed, Although the CO2 footprint of CFA and activated carbon is comparable, CFA shows an extremely lower embodied energy with respect to activated carbon, the most used widely used material for surfactant removal. Surfactant are widely used in several detergents products, and enter into the environment through the discharge of sewage effluents. In this paper, Sodium Dodecyl Sulfate (SDS) is used as a model surfactant. Upon careful optimization of the CFA/SDS mass ratio, it was found that CFA is able to remove SDS from water with efficiency up to 96%. SDS adsorption onto the CFA surface was investigated and results point to a three-step mechanism, which stops with the final formation of a CFA supported SDS bilayer. There are two main results: first, the first one in the era of raw materials scarcity, the choice of to investigate the employ employment of a material in terms of its embodied energy must be considered; second, the second result this work opens new perspectives in the field of anionic surfactant removal. Graphical abstract: Image 1 Highlights: To evaluate the sustainability of a specific material, embodied energy can be considered. The embodied energy of coal fly ash is lower than the one of other adsorbent materials for surfactant. The coal fly ash adsorption mechanism is identified.